Pelatihan Pemasaran Digital sebagai Upaya Pemberdayaan Ekonomi Masyarakat Desa di Kecamatan Subang, Kabupaten Subang - Karyono Karyono; Siti Mujanah; Ekbal Santoso (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
The Community Service activity (PkM) with the title “Digital Marketing Training as an Effort to Empower the Economy of Village Communities in Subang District, Subang Regency ”* aims to increase the knowledge and skills of Micro, Small and Medium Enterprises (MSMEs) in Subang District Village in utilizing digital technology for marketing their products. The methods used in this training include the provision of digital marketing theory materials, practice in using digital platforms (such as social media and e-commerce), and evaluation through pre-test and post-test. In conclusion, the training was successful in empowering village communities through the application of digital marketing. The sustainability of similar programs as well as the development of further training modules are expected to further strengthen the digitalization capabilities of MSMEs in the region, thus contributing to the improvement of the overall economic welfare of the community